Quality of colon carcinoma pathology reporting: A process of care study - Wei, Jeffrey T.; Miller, Eric A.; Woosley, John T.; Martin, Christopher F.; Sandler, Robert S. (Cancer, 2004)
In 1996, the Association of Directors of Anatomic and Surgical Pathology (ADASP) published recommendations for colon carcinoma reporting. Since this publication, no study has evaluated physician practice in relation to these recommendations. The objectives of the current study were to describe pathology reporting for colon carcinoma, evaluate potential variations in reporting, and identify areas for improvement. Data were obtained from a population-based study of incident colon carcinoma in 33 counties in North Carolina between 1997 and 2000. All subjects with surgically resected colon carcinoma of tumor stage T2-T4 with available surgical pathology reports were eligible for inclusion in the current analysis. The authors reviewed pathology reports for adherence to recommendations of the ADASP. Four hundred thirty-eight pathology reports were included for analysis. Adherence to ADASP recommendations was < 90% for descriptions of how specimen was received (68%), how specimen was identified (71%), macroscopic depth of penetration (82%), appearance of serosa adjacent to tumor (50%), and status of residual bowel (73%). All other criteria were reported in > 90% of patients. Teaching hospital and contract pathology laboratories had greater adherence to recommendations, compared with community hospital laboratories. Hospitals with the highest colon carcinoma case volume demonstrated greater adherence to recommendations, compared with low-volume hospitals. Pathology reports were effective in communicating most pertinent findings from surgically resected colon carcinoma specimens. Omissions of some critical characteristics did occur, however, and significant variability in reporting existed based on laboratory affiliation and hospital case volume.